Azorean savings banks and the 1929 economic crisis - Lopes, Fernando Rosa Rodrigues (2019)
What sets the Azorean banking system apart in the Portuguese context is the concentration of Caixas Económicas or Saving Banks accounting for half of these financial institutions in Portugal. These saving banks were promoted and had as shareholders mainly small and medium local traders and landlords with export business. This contrasts with the overwhelming concentration of big traders and traditional landlords as agents of international and national banks. These small institutions were the only network covering most of the islands and preceded the expansion of a national bank network of agencies created mostly after the Second World War. This article examines the effects of the 1929 crisis on the Azorean banking system which was generalized, and had deep and long-lasting effects, using unpublished data taken from the archive of Banco de Portugal. It is a case of contagion, typical of a banking crisis, affecting the credibility and confidence of all the institutions and leading to an interruption of payments for a period of over two years. Bankruptcies are limited to Caixa Bancária Raposo do Amaral and Caixa Económica Socorros Mútuos but the restructuring spreads over a ten year period. The contraction of monetary circulation caused by the banking crisis and the elimination of escudo insulano are also major contributing factors to the long and deep economic crisis that spread from 1929 to 1945. The banking crisis together with the protectionism of European markets and Portuguese colonial policies lead to the reorientation of the agro-export model to mainland Portuguese markets.